2018
DOI: 10.1177/1354068817749777
|View full text |Cite
|
Sign up to set email alerts
|

Who do you believe? Political parties and conspiracy theories in Pakistan

Abstract: In authoritarian states, emerging democracies, and well-established democracies alike, alternative accounts that contest official state narratives are common. Why do people believe such accounts even in the absence of supporting evidence? While this question has been explored in the United States, relatively little research has assessed it in other contexts. Through a survey experiment carried out in Pakistan, this article tests the impact of cues by political parties on belief in such conspiracy theories. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Further, more work must examine how these scales translate across geographic context, particularly into closed societies where the conspiracy theories about government are likely to be more rational. The study of conspiracy theories is beginning to traverse geographic boundaries; for example, see works on Turkey (Nefes, ), Russia (Yablokov, ), Europe (Drochon, ), the Middle East (Nyhan & Zeitzoff, ; Siddiqui, in press), Latin America (Filer, ), and Thailand (Greenhill & Oppenheim, ). Studies should begin integrating these various findings to develop broader theories.…”
Section: Definitionsmentioning
confidence: 99%
“…Further, more work must examine how these scales translate across geographic context, particularly into closed societies where the conspiracy theories about government are likely to be more rational. The study of conspiracy theories is beginning to traverse geographic boundaries; for example, see works on Turkey (Nefes, ), Russia (Yablokov, ), Europe (Drochon, ), the Middle East (Nyhan & Zeitzoff, ; Siddiqui, in press), Latin America (Filer, ), and Thailand (Greenhill & Oppenheim, ). Studies should begin integrating these various findings to develop broader theories.…”
Section: Definitionsmentioning
confidence: 99%
“…Differences in living areas which cause individuals to be more or less physically isolated from others have also been proposed to be predictive of CT belief. Again, some studies found individuals living in remote or rural areas to adhere more to CT beliefs (Mari et al., 2022; Siddiqui, 2020), while others did not (Sternisko et al., 2021). Socio‐economic factors like income and—more generally—SES may also serve as potential predictors of CT belief.…”
Section: Introductionmentioning
confidence: 99%
“…People are not equally prone to conspiracy thinking, so what explains people’s propensity to conspiracy thinking? Most work on conspiracy beliefs examines a single context, primarily the United States (Enders and Smallpage, 2018, for non-US single country studies, see, for example, Hogg et al, 2017; Jasinskaja-Lahti and Jetten, 2019; Krouwel et al, 2017; Mancosu et al, 2017; Siddiqui, 2020; Swami, 2012). However, even when studies are conducted in different contexts, many are based on different concepts, operationalizations and analytical approaches, thereby making systematic comparison problematic (Nyhan and Zeitzoff, 2018 is the exception).…”
Section: Introductionmentioning
confidence: 99%